2020
DOI: 10.1109/lra.2019.2945261
|View full text |Cite
|
Sign up to set email alerts
|

Online Identification of Interaction Behaviors From Haptic Data During Collaborative Object Transfer

Abstract: Joint object transfer is a complex task, which is less structured and less specific than what is existing in several industrial settings. When two humans are involved in such a task, they cooperate through different modalities to understand the interaction states during operation and mutually adapt to one another's actions. Mutual adaptation implies that both partners can identify how well they collaborate (i.e. infer about the interaction state) and act accordingly. These interaction states can define whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…Using a random forest classifier, we verified that haptic information, i.e., wrenches, was sufficient to differentiate between the interactions patterns. This contrasts with our earlier work [25], [26], which suggested that kinematic information is needed to improve classification rates in distinguishing between interaction patterns in dyadic co-manipulation. In this work, we have demonstrated that using carefully devised haptic-related metrics derived from raw data eliminates the dependency on kinematics.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Using a random forest classifier, we verified that haptic information, i.e., wrenches, was sufficient to differentiate between the interactions patterns. This contrasts with our earlier work [25], [26], which suggested that kinematic information is needed to improve classification rates in distinguishing between interaction patterns in dyadic co-manipulation. In this work, we have demonstrated that using carefully devised haptic-related metrics derived from raw data eliminates the dependency on kinematics.…”
Section: Discussioncontrasting
confidence: 99%
“…In future work, we will use the proposed features with online classification as proposed in [26], and develop a system that identify the current interaction state in real-time during collaboration. Although this experiment does not cover all the human-human interaction patterns, this information will be useful when programming a robot partner that reads interaction states and reactively acts in response to the predicted behaviors, which is the ultimate goal of this research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle this, active learning mechanisms can be integrated in the current framework to enable iterative learning to enrich the robot's behaviour library. In addition, extending on our recent work [36], [37], we plan to integrate active conflict recognition within this framework, and as a result, handle not only collaborative but also conflicting scenarios in physical human-robot interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to develop an approach to estimate the parameters of human biomechanics and track them in real-time as they vary. Furthermore, it is crucial to create a method that allows recognizing the current interaction mode in real-time using the data acquired by on-board sensors [38]. By knowing the interaction mode, an appropriate cost function can be defined, and the automation system can adjust its behavior based on this cost function.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%